A proposed protocol for the management of COVID-19 in Egypt - Sorour, Khaled; El-Menshawy, Hadeer (My University, 2020)
As regarding the current pandemic, there is no definitive treatment for COVID-19, the attached protocol does not mean a recommendation for treatment, but for a clinical trial to validate the safety and efficacy of this combination.
Keywords: ARDS; Clinical trial; COVID-19; SARS-CoV-2; Treatment protocol